Democracy, Religion, and Pluralism Theological responses - Guggenberger, Wilhelm; Kumar Hrudayaraj, Bala Kiran (innsbruck university press, 2022)
Democracy seems to be endangered. In the face of growing inequalities propelled by neo-liberal free-market mechanisms, hyper-nationalist movements have emerged across the world, manifesting deep-seated resentment and anger among large sections of people that have telling consequences on the democratic practices. In such a volatile context, this volume is in search of a biblical founded theological and ethical position to populism, nationalism and post-democratic positions. Drawing upon Catholic Social Thought and socio-political insights, the particular articles respond to current developments in an international context. The offered catholic theological reflections hope to highlight new insights and narratives that have potential to foster the deepening of democracy and democratic values.